Decoding Support for Pitha Limcharoenrat: A Quantitative Study on the Role of Political Challenges, Media Influence, and Public Perception Among Thai Voters in the USA - Hastindra Na Ayudhaya, Narupollawat; Kulachai, Waiphot; Phisuthisuwan, Phakawanaporn (Program Studi Teknologi Rekayasa Informasi Pemerintahan, 2024)
The variables affecting Thai voters living in the United States in their support for Pitha Limcharoenrat are investigated in this paper. Using data from 396 respondents gathered via an online poll, it emphasizes the roles of political problems, media impact, and public opinion, therefore reaching a distributed demographic efficiently. Multiple regression was used in the analysis, and the JAMOVI program was used to achieve a robust model fit (R2 = 0.583). This model fit accounts for 58.3% of the variance in voter support. It was found that public opinion was the most influential predictor among the factors (normalized value = 0.457), followed by the influence of the media (0.297) and political problems (0.117s). These results highlight the need of public opinion and media coverage in forming political support among the Thai diaspora in the United States, therefore providing insightful information for policies meant to involve expatriate populations. Keywords: Diaspora, Media Influence, Public Perception, Voter Support.